Training and Institutional Guidelines in Teachers’ Adoption of Generative Artificial Intelligence: Bibliometric Analysis, Empirical Evidence, and Implications for Quality Education and Sustainable Development Goals (SDGs) - Majda Mountacer; Nafidi Youssef (Bumi Publikasi Nusantara, 2027)
Generative artificial intelligence (GenAI) is increasingly shaping educational practice, yet teachers’ professional adoption remains uneven. This study examines the roles of AI-related training and institutional guidelines in teachers’ use of GenAI and situates the findings within the broader context of quality education and the Sustainable Development Goals (SDGs). A cross-sectional survey of 208 Moroccan teachers was analyzed using descriptive statistics, bivariate tests, and binary logistic regression, complemented by a concise bibliometric overview of GenAI research trends. AI-related training was significantly associated with professional GenAI use, whereas institutional guidelines were not significant after adjustment. The findings emphasize the importance of sustained professional development and provide evidence for strengthening responsible GenAI integration in education, particularly in support of SDG 4 on quality education.